2022
DOI: 10.37256/ser.3320221402
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Digital Technologies in Higher Education during the Coronavirus Pandemic: Insights from a Ghanaian University

Abstract: The emergence of the coronavirus disease saw the closure of schools as well as a hitch in the application of the face-to-face approach to classroom interaction. During this period, digital technologies presented a useful alternative. In the present study, we examined the use of digital technologies among students of the University of Cape Coast during the coronavirus pandemic. The study relied on a qualitative research design involving interviews with 10 students. The findings revealed that students used mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…TAM indicates that PU and PEOU predict the intention to use a particular technology. Interestingly, the intention to use technology determines the actual use of technology (Agbaglo & Bonsu, 2022). Conversely, technology acceptance and use currently appear problematic for most higher educational institutions (Noble et al, 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…TAM indicates that PU and PEOU predict the intention to use a particular technology. Interestingly, the intention to use technology determines the actual use of technology (Agbaglo & Bonsu, 2022). Conversely, technology acceptance and use currently appear problematic for most higher educational institutions (Noble et al, 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It is unclear whether mass use or actual integration into higher education determines the acceptance and usage. Despite this weakness, the theory has been widely tested and adopted in educationally inspired studies (Agbaglo & Bonsu, 2022;Fathema et al, 2019;Gyamfi, 2016;Tlili et al, 2023;Williams et al, 2022). There is a growing interest in adopting several technologies in higher educational institutions in developing countries, such as Ghana (Afari, & Achampong, 2010;Anamoah-Mensah, 2011;Buabeng-Andoh, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Both [25,26] identified some common gadgets for the facilitation of online tutoring as laptops, desktop computers, cell phones, smartphones, tablet apps, iPads, iPods, iPhones, and video cameras. In a case study by [27], the consequences of the digital technology utilized to support instruction and learning in Ghana during the COVID-19 pandemic have been examined. Their study revealed that students largely used mobile phones and laptops to access video conferencing platforms such as Zoom, WhatsApp, Google Meet, Teams, and Skype.…”
Section: Distance Education and Onlinementioning
confidence: 99%
“…In the realm of higher education, the digital revolution has become an integral and enduring force. Notably, the COVID-19 pandemic has accelerated the adoption of digital tools such as mobile technologies and online meeting platforms, making them indispensable (Agbaglo & Bonsu, 2022).…”
Section: Introductionmentioning
confidence: 99%